Tashkent, Bukhara and Khorezm republics, epidemics, and fight against them - Karomov G’. Kh (Indonesian Journal of Innovation Studies, 2019)
The article concludes that the outbreak of epidemics is a major factor in the poor living conditions of the population. In human history, epidemics are a real catastrophe for the population, which is based on the fact that wars, natural conditions, coastal and famine-stricken factors are its companions. History tells about the "Justinianova chuma" spread throughout the Eastern Roman Empire, the "Black Death" epidemic in Europe, and the Spanish flu after the First World War. The population of Central Asia has been suffering from epidemics since ancient times due to hot climatic conditions and other factors. Turkistan is one of the main sources of the cholera and malaria epidemic, and in 1881 it was mentioned in New Marghilan and in 1898 in Tashkent. Health care in Turkestan, Bukhara and Khorezm is accompanied by sanitary and epidemic work, but the difficult historical conditions, particularly political, socioeconomic problems, poor living conditions and civil war. It is also noted that droughts caused by natural disasters and, as a consequence, famine have spread epidemics. Frequent medical and sanitary measures to fight epidemics sociation units. The Turkestan ASSR Public Health Commission operated the Department of Medical Education and Sanitation, and the staff of the department was propagandizing the fight against the epidemic. Based on the results of the study, it is concluded that in each state, the most important factor in preventing epidemics is to improve living conditions and to increase public health education.